STRUKTUR GOOD CORPORATE GOVERNANCE SEBAGAI PEMODERASI PENGARUH ASIMETRI INFORMASI PADA MANAJEMEN LABA - Kori, Opyandari Dharsini; Rasmini, Ni Ketut (E-Jurnal Akuntansi; Vol 21 No 1 (2017), 2017)
The study examined the structure of Good Corporate Governance as a moderating influence on earnings management information asymmetry. The purpose of this study to determine (1) the effect on earnings management information asymmetry, (2) the interaction effect of good corporate governance structure on earnings management. The population of this research is manufacturing companies listed in Indonesia Stock Exchange (BEI) in the period 2010-2015. The number of samples of this research are 22 companies with 132 the data of observation. The samples in this study using non-probability method with purposive sampling technique by using specific criteria for the selection of the sample. Data were analyzed using Moderated Regression Analysis (MRA). The results showed that the information asymmetry effect on earnings management. In addition the results of this study also shows that institutional ownership of good corporate governance structure able to moderate influence on earnings management information asymmetry, while other proxy includes independent directors, board size, the audit committee was not able to moderate the influence of asymmetry of information on earnings management.
Keywords: Information Asymmetry, Independent Commissioner, Size of Commissioners, Audit Committee, Institutional Ownership, Earning Management